Tejano proud : Tex-Mex music in the twentieth century - San Miguel, Guadalupe, 1950- (Fronteras series, 2002)
Chronicles the history of Tex-Mex music in the twentieth century, discussing its origins in Mexican culture, the diversity and complexity of the music, its importance to Mexican Texas culture in the context of Anglo-Mexican relations.